UNVEILING THE ROOTS OF ENDURING COMMUNAL CONFLICTS IN NIGERIA: INDIGENE-SETTLER RIVALRY AND THE PATH FORWARD - MICHEAL GODWIN OKOLIKO (International Studies Journal)
The enduring conflict between indigenes and settlers in Nigeria has escalated over time, resulting in persistent and often violent communal disputes. These conflicts have inflicted significant harm, including widespread community devastation, loss of life, displacement of millions, and severe human rights violations, particularly impacting vulnerable populations like women and children. Despite governmental efforts to mitigate these conflicts, the fundamental issues remain largely unaddressed, with governance structures often struggling to manage the crises effectively and provide lasting solutions. This article examines the underlying factors contributing to intra/inter-communal conflicts arising from indigene and settler rivalries in Nigeria, utilizing the lens of elite theory. By comprehensively analyzing these factors, a deeper understanding of the intricate dynamics at play is gained, allowing for the identification of potential avenues for meaningful intervention. This study adopts qualitative research design to arrive at its conclusion, finding and recommendation. It is imperative to recognize that these conflicts are deeply entrenched in historical, social, economic, and political factors that have shaped Nigeria's societal landscape.